2017
DOI: 10.1177/1359105317733321
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the bigger picture: Young men’s sexual health from a psychological perspective

Abstract: Researchers have seldom compared how various psychological factors relate to men's sexual health. We sought to identify whether and how psychological risk factors (i.e. anxiety sensitivity, emotion regulation, psychological distress) predict men's sexual health (i.e. functioning, sexual quality of life, frequency of sexual activity). Men ( N = 306) completed an online survey measuring emotional, psychological, and sexual outcomes. Comparisons of four path analysis models suggested that psychological risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…28 Thus, the mean score we observed for women (78) may be somewhat lower than expected. Among 306 Canadian male university students of mean age 20 years, the mean raw SQoL-M score was 49.6, 35 and 53.8 among 181 Iranian men with mean age 35 years. 26 For comparison, the mean raw baseline SQoL-M score in our study was 59.2, much higher than scores derived from other relatively young and healthy male populations.…”
Section: Discussionmentioning
confidence: 97%
“…28 Thus, the mean score we observed for women (78) may be somewhat lower than expected. Among 306 Canadian male university students of mean age 20 years, the mean raw SQoL-M score was 49.6, 35 and 53.8 among 181 Iranian men with mean age 35 years. 26 For comparison, the mean raw baseline SQoL-M score in our study was 59.2, much higher than scores derived from other relatively young and healthy male populations.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the construct of anxiety sensitivity (i.e., the fear of anxiety-related sensations because of their potential harmful consequences; Reiss & McNally, 1985) was also instrumental in developing evidence-based cognitive behavioral interventions for panic disorder. Correlational research suggests that anxiety sensitivity is associated with greater sexual functioning difficulties in both women (Gerrior, Watt, Weaver, & Gallagher, 2015;Tutino, Ouimet, & Shaughnessy, 2017) and men (Tutino, Shaughnessy, & Ouimet, 2018). Experimental research manipulating anxiety sensitivity (e.g., by inducing beliefs about physiological sensations and their consequences) is greatly needed to determine whether anxiety sensitivity impacts sexual arousal and other aspects of the sexual response.…”
Section: Discussionmentioning
confidence: 99%
“…months (Choudhry et al, 2014) or even in the last 3 months (Carney et al, 2019); inconsistent condom use with new partners (Carney et al, 2019, Choudhry et al 2019, Agardh et al 2012a); sexual assault and/or coercion (Davis et al 2012; Choudhary, Smith, & Bossarte, 2012); commercial and intergenerational sex (Choudhry et al, 2014).Analyzing the gender difference,Breet et al (2019) found that boys had a tendency almost 2 times higher (42.9%) than girls (23.8%) to commit sexual coercion. At the same time,Tutino et al (2018) found that mental health difficulties can have a greater impact on men's sexual functionality and quality of sex life.…”
mentioning
confidence: 99%